Comparative evaluation of elastic recovery of three different elastomeric impression materials on chemical disinfection and autoclaving: An in vitro study - Garima Gothwal; Sudhir Meena; U Narendra Padiyar; Hemant Kumar Sharma; Pragati Kaurani; Devendra Pal Singh (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study was to investigate the effect of disinfection and steam autoclaving on the elastic recovery of three different elastomeric impression materials. Settings and Design:In vivo - comparative study. Materials and Methods: Ninety dumbbell-shaped specimens of commercially available two addition-cured silicones (AFFINIS and AQUASIL) and one condensation-cured silicone (SPEEDEX) impression materials were prepared and treated with chemical disinfectant and steam autoclaving. Specimens were seal packed and sent to laboratory for testing elastic recovery. After the specimen had been pulled to failure, the broken parts were fitted back together, and the distance between the marks was measured using an electronic Vernier caliper. Statistical Analysis Used: one-way analysis of variance test and Tukey post hoc test for multiple comparisons. Results: The result showed significant difference in elastic recovery of AFFINIS when it was disinfected and steam autoclaved whereas elastic recovery showed no significant difference when SPEEDEX and AQUASIL were disinfected and steam autoclaved. Similarly, results were alike when AFFINIS, SPEEDEX, and AQUASIL were compared on disinfection. However, significant difference was noted on steam autoclaving, highest being the mean value of AFFINIS. Conclusion: Within the limitations of this in vitro study, conclusion was made that the elastic recovery of AFFINIS was the least which improved with disinfection and autoclaving. Elastic recovery of SPEEDEX and AQUASIL was similar. However, all the three materials used in the study can be safely sterilized after clinical use and before being sent to the laboratory without significantly affecting their elastic recovery.